The Effect Of Intellectual Capital On Banking Stability: The Role Of Board Education Characteristics - Dwi Hari Prayitno; Rochman Arif; Fitri Nurjanah; Akhmad Imam Amrozi; Mohammad Syafik (Journal of Economics and Business (JECOMBI), 2025)
The purpose of this study is to examine the influence of intellectual capital, namely human capital, structural capital and relational capital on banking stability with the moderating role of top management education characteristics. A total of 166 observation data were sampled in this study. Data analysis used moderate regression analysis. The results showed that all three components of intellectual capital had an influence on banking stability. Meanwhile, if the moderating effect of top management education characteristics was added, only human capital had no effect. While structural capital and relational capital remained consistent in having a positive effect on banking stability.